2019
DOI: 10.1536/ihj.17-283
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Proximal Seal System on Neurologic Outcomes of Off-Pump Coronary Artery Bypass Grafting

Abstract: Severe aortic atherosclerosis is a risk factor for stroke during coronary artery bypass grafting (CABG). The purpose of this study was to evaluate the incidence of postoperative neurologic complications after off-pump CABG (OPCAB) with a proximal seal system (Heartstring). From January 2011 to December 2014, 729 patients underwent isolated OPCAB. The cohort was divided into two groups (Heartstring [HS] and aortic no-touch [NT]). The severity of aortic atherosclerosis (Katz grade) was evaluated by intraoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…15 Recently, Kim and colleagues also reported no significant differences in hospital mortality, perioperative stroke, and MACCE, and equivalent 5-year survival rates between the two groups, Heartstring (n ¼ 323) and aortic no-touch (n ¼ 406) undergoing isolated CABG. 21 Although these studies reported acceptable late outcomes with Heartstring, no studies investigated the predictors of late death as our study did.…”
Section: Discussionmentioning
confidence: 62%
“…15 Recently, Kim and colleagues also reported no significant differences in hospital mortality, perioperative stroke, and MACCE, and equivalent 5-year survival rates between the two groups, Heartstring (n ¼ 323) and aortic no-touch (n ¼ 406) undergoing isolated CABG. 21 Although these studies reported acceptable late outcomes with Heartstring, no studies investigated the predictors of late death as our study did.…”
Section: Discussionmentioning
confidence: 62%
“…In 3 studies, aortic atherosclerosis was identified as an independent predictor using multivariate regression analyses [ 52–54 ]. This correlation was not observed in 2 studies evaluating the use of a clampless proximal anastomosis facilitating device [ 55 , 56 ]. Apparently the use of these devices helps to prevent the increase in stroke rate associated with increasing aortic atherosclerosis severity.…”
Section: Coronary Artery Bypass Graftingmentioning
confidence: 88%
“…Delirious patients often remove intubation and infusion tubes from the body, which seriously threatens the safety of patients' lives. For the occurrence of postoperative delirium, current research has confirmed many factors including major bleeding during surgery, hemodynamic instability, and the patient's history of cerebrovascular disease [47][48][49][50][51] . However, there is still a lack of a systematic and effective prediction system, thence it is of great significance to explore and study the prediction scoring system for delirium following OPCABG.…”
Section: Discussionmentioning
confidence: 99%